Divided attention enhances explicit but not implicit conceptual memory: an item-specific account of the attentional boost effect. Issue 2 (7th February 2017) - Spataro, Pietro; Mulligan, Neil W.; Bechi Gabrielli, Giulia; Rossi-Arnaud, Clelia
ABSTRACT: The Attentional Boost Effect (ABE) refers to the counterintuitive finding that words encoded with to-be-responded targets in a divided-attention condition are remembered better than words encoded with distractors. Previous studies suggested that the ABE-related enhancement of verbal memory depends upon the activation of abstract lexical representations. In the present study, we extend this hypothesis by embedding it in the context of a broader perspective, which proposes that divided attention in the ABE paradigm affects item-specific, but not relational, processing. To this purpose, we examined the ABE in the matched tasks of category-cued recall (CCRT: explicit memory) and category exemplar generation (CEGT: implicit memory). In addition, study time was varied (500, 1500 or 4000 ms), to further determine whether the attentional boost manipulation could influence late-phase elaborative processing. In agreement with the predictions of the item-specific account, the results showed that exemplars encoded with targets were recalled better than exemplars encoded with distractors in the CCRT, but not in the CEGT. Moreover, performance in the CCRT increased with study time, whereas the size of the ABE-related enhancement tended to decrease, further confirming that this effect hinges upon early phase encoding processes.